Lessons from the COVID-19 epidemic in Hubei, China: Perspectives on frontline nursing. Issue 5 (September 2022) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Zhao, Jie; Butt, Laveeza; Saran, Ravneet; Lam, Simon Kwun Yu; Thompson, David R.
Background: The emergence of COVID-19 has been an ordeal for nurses worldwide. It is crucial to understand their experiences at the frontline, attempt to allay their concerns, and help inform future pandemic response capabilities. Aims: To explore nurses' lived experiences at the frontline in order to identify and address their concerns and help enhance future responses to infectious disease outbreaks. Methods: A qualitative study was carried out. Semi-structured interviews were conducted with 60 registered nurses who came to Hubei from different parts of China to care for patients with COVID-19. Interviews were audio-recorded and transcribed verbatim for thematic analysis. Results: Six major themes emerged: emotional turmoil due to personal and professional concerns, quality issues with personal protective equipment and associated physical discomfort, witnessing and managing patient distress, readiness of emergency response mechanisms in the health system, collective community awareness and preparedness, and heightened professional pride and confidence in future epidemic control. Discussion: Nurses were placed in challenging and unfamiliar situations to deal with unexpected and unpredictable events which caused considerable psychological and physical distress. Support in the form of government edicts, hospital management policies, community generosity and collegiality was highly welcomed by the nurses. Policy makers and managers should ensure that nurses are provided with the support and resources necessary for dealing with large-scale infectious disease outbreaks. Priority should be given to risk assessment, infection prevention and control, and patient and staff health and safety.